Positive and Negative Sentiment of Artificial Intelligence in Language: Study Prompt on Chat GPT - Wildan, M (Universitas Pamulang, 2024)
The study explored both positive and negative sentiments towards artificial intelligence in language, focusing on study prompts using Chat GPT. The goal of this study is to understand how users perceive and judge AI in the context of language models such as Chat GPT. The research method used is qualitative descriptive, which focuses on prompts aimed at bringing up language facts. Data collection is carried out through a prompt submission which is then responded to by Chat GPT. Data analysis was carried out using a narrative analysis approach. It is intended to identify patterns of positive and negative sentiment in the responses given by Chat GPT. The results of the study showed that there was a Chat GPT response that led to positive and negative sentiment. The prompts